Oral Manifestations of Celiac Disease and Wheat Allergy: Report of Three Cases and Review of Literature - Boza Oreamuno, Yadira V. (2018)
Celiac Disease (CD) is an immune-mediated systemic disease, caused by gluten and related prolamins, in genetically susceptible individuals. It is characterized by gluten-dependent clinical manifestations, CD-specific antibodies, HLA DQ2 or DQ8 haplotypes, and enteropathy. Most patients are asymptomatic or with mild manifestations. It mainly affects the gastrointestinal system causing symptoms and signs such as diarrhea, recurrent abdominal pain and abdominal distension; also extradigestive manifestations. Patients with CD may have oral manifestations that include recurrent aphthous stomatitis (RAS), enamel hypoplasia, atrophic glossitis, among others. The diagnosis of CD is based on clinical history, serology, endoscopy and histology. There are other entities that should be differentiated from CD, such as non-celiac gluten sensitivity and wheat allergy. The aim of this study is to present three patients with a history of RAS and other clinical manifestations associated with the early diagnosis of CD and food allergy.